PUBLIC SPEAKING DAN KONSTRIBUSINYA TERHADAP KOMPETENSI DAI - Siti Aisyah (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2017)
Public speaking is an activity that aims to provide an information, affection and even entertain the audience. Likewise with da'wah activities where this activity is done by daito persuade good and avoid bad things to mad’u. This paper will discuss about the contribution of public speaking for daicompetence. The existence of public speaking or the art of speech daiis able to increase the smoothness of da'wah activities significanly. To carry out da'wah activities need the knowledge and preparation, so to achieve that, daineeds for mastery of both, whether daicompetence or public speaking in terms of the materials, techniques and maturity